Aid, Terrorism, and Foreign Direct Investment: Empirical Insight Conditioned on Corruption Control. Issue 4 (2nd October 2018) - Efobi, Uchenna; Asongu, Simplice; Beecroft, Ibukun
ABSTRACT: This paper checks the effect of foreign aid on terrorism–foreign direct investment (FDI) nexus, while considering the extent of domestic corruption control ( CC ). The empirical evidence is based on a sample of 78 developing countries. The following findings were established: the negative effect of terrorism on FDI is apparent only in countries with higher levels of CC ; foreign aid dampens the negative effect of terrorism on FDI only in countries with high level of CC . Also, the result is mixed when foreign aid is subdivided into its bilateral and multilateral components. While our findings are in accordance with the stance that bilateral aid is effective in reducing the adverse effect of terrorism on FDI, we find that multilateral aid also decreases the adverse effect of other forms of terrorism that can neither be classified as domestic or transnational. Policy implications are discussed in the paper.